Is Software the Result of Top-Down Intelligent Design or Evolution? Considering the potential danger to individuals of rapid coevolution. - Lee, Edward A. (Communications of the ACM, 2018)
The author argues that software technologies are evolving, or co-evolving with human culture, versus software engineers having full control over their designs. Topics include the influence of previous software programs and cultural forces on the development of new software, the influence of human decision making on the evolution of software programs, and concerns regarding human reliance on intelligent machines.